A study of the relationship between soil and quantitative terrain factors - Bruce, Romeo C.
The objective of the study was to determine whether or not different soil areas in Hawaii could be separated by means of quantitative terrain factors. Eight great soil group areas on Oahu and six soil association areas on Kauai were selected. A sufficient number of 0.5-mile square test cells was established at random in each of the test soil areas. Ten terrain factors were quantified in each of the test cells from data measured on either the topographic maps or the aerial photographs or both. The results showed that certain great soil groups on Oahu and certain soil associations on Kauai can be differentiated by their quantitative terrain factors. Average elevation, local relief, average slope, slope length, land texture ratio and drainage density were found effective in differentiating between these different groups and associations. Four terrain factors has been found effective in separating the Haplustox, Eutrorthox and Gibbsihumox areas on Oahu. These factors, in the order of decreasing effectiveness, were average slope, drainage density, slope length and local relief. The discriminant function equation developed for Tropohumult and Gibbsihumox areas, based on average elevation, average slope, slope length and drainage density, has satisfactorily segregated the two soil areas on Oahu. The results of the numerical grouping analysis of 108 test cells established in 0.5-mile grids in eastern Kauai indicated that numerical methods on the basis of several terrain factors has much to offer in reconnaissance soil surveys of large, relatively undeveloped regions where information about the soil is not available.